(untitled) (Journal of the College of Basic Education, 2022)
This research aims to study some of the most important planning legislation in managing the urban environment in Iraq, and to identify the reflection and impact of those legislation on the structure and formation of the Iraqi city, and whether the deterioration in the urban environment was due to deficiencies in legislation, or to the weakness of urban management. It became clear through the research that the planning legislation has a great impact on the structure of the city, and the organization of land uses in it, especially in the residential sector, and that some of these legislations had contributed to the deterioration of the urban environment. It also became clear that the urban administration, which bases its work on these legislations, had a weak role and was not at the level that prevents the deterioration of the urban environment, in addition to the multiplicity of agencies responsible for urban management with more than one executive ministry.